Investigation of toxicity effect of TiCN coated on 304 SS and 410 SS substrates in rat fibroblasts and B-lymphocytes. Issue 2 (16th March 2022) - Naserzadeh, Parvaneh; Razmi, Abbas; Yesildal, Ruhi; Ashtari, Behnaz
Abstract: In the present study, TiCN thin films were coated on AISI 304 and AISI 410 stainless steel (SS) substrates by Cathodic Arc Physical Vapor Deposition method. TiCN-coated substrates were confirmed by the XRD analysis results. Dense morphology and fine-grained surface of TiCN film were established by SEM images. Cellular toxicity of the coated 304 SS and 410 SS substrates was investigated in the fibroblasts and B-lymphocyte. In respect to that, we have shown coated substrates cytotoxicity, oxidative stress as well as cell viability, reactive oxygen species (ROS), lipid peroxidation (MDA), protein carbonyl, glutathione oxidase (GSSG), and glutathione reductase (GSH) assessment, releasing cytochrome c (Cytc), lysosomal membrane destabilization (AO) may lead to cell death signaling. Our results showed that the coated 304 SS and 410 SS substrates induced cells dysfunction via a significant increase in ROS production, MDA ( P  < 0.01 and P  < 0.001), protein carbonyl ( P  < 0.05), and GSSG ( P  < 0.05 and P  < 0.01) that correlated to cytochrome c release ( P  < 0.01). In addition, increased disturbance in oxidative phosphorylation was also shown by the decrease in cell viability ( P  < 0.001) and GSH ( P  < 0.01 and P  < 0.001) in the coated 304 SS and 410 SS substrates-treated fibroblast and B-lymphocytes. The coated 304 SS and 410 SS substrates contacted cells and trafficked to the lysosomes and this is followed by lysosomal damage, leading to apoptosis/Necrosis. Our results indicated that these materials cause cellular dysfunction and subsequent oxidative stress leading to cognitive impairment in the rat fibroblasts and B-lymphocytes cells. Graphical Abstract: